Performance and Cost Comparison of Building Structures with SRPM and Shearwall in Seismic Dynamic Analysis - Qur’ani, Difla Yustisiya; Sulaksitaningrum, Roro (Newinera Publisher, 2025)
As a country located on the Pacific Ring of Fire, Indonesia faces a high seismic risk, necessitating the design of earthquake-resistant buildings. This study evaluates the seismic performance and cost implications of multi-story U-shaped buildings using the Moment Resisting Frame System (SRPM) and shear walls. Four structural models with different configurations were analyzed using ETABS 22 for structural behavior and Microsoft Excel for cost estimation. The results indicate that models with shear walls exhibit better lateral stiffness, resulting in shorter fundamental periods and smaller interstory drifts. Model 2 demonstrated the best seismic resistance, making it the primary choice for earthquake-prone areas. However, the cost analysis showed that models without shear walls, particularly Model 4, were more economical. While shear walls increase initial construction costs, they offer long-term benefits by reducing potential structural damage and post-earthquake maintenance costs. This study provides valuable insights into balancing seismic safety and cost efficiency, assisting in the selection of the optimal structural system for earthquake-prone regions.